Effects of External Auditory Meatus Occlusion on Ocular Vestibular Evoked Myogenic Potentials Induced by Bone Conducted Sound - Murofushi, Toshihisa; Ohki, Masafumi; Tsubota, Masahito (Frontiers in Neurology, 2021)
To facilitate more reliable recordings of the ocular vestibular evoked myogenic potentials (oVEMP) induced by bone-conducted sound using the B81 bone conduction transducer, we preliminarily studied the effects of external auditory meatus occlusion using an earplug on such oVEMP. Eight healthy volunteers (4 males and 4 females, 26-48 years of age, mean age: 34.5 years) and 14 patients with vestibular disease (2 males and 12 females, 18-59 years of age, mean age: 41.5 years) were enrolled. oVEMP testing was performed using a B81 placed on the temple. Tone bursts (500 Hz, rise/fall time: 2 msec, plateau time: 2 msec, 70 dB nHL) were presented at a rate of 5.1 Hz. N1-P1 amplitudes were measured and analyzed. Occlusion resulted in significantly larger N1-P1 amplitudes (meanSE(SD): 12.31.67 (6.71) μV vs. 9.551.55 (6.21) μV; p=0.020, paired t-test). While 4 patients did not exhibit any response on either side in the absence of occlusion, all of them showed unilateral or bilateral responses when occlusion was employed. In any patient occlusion did not result in loss of oVEMP responses. External auditory meatus occlusion using an earplug could allow more reliable recordings of bone conduction transducer-induced oVEMP.